Minat Generasi Muda Dalam Berinvestasi Reksadana Syariah - Adawiah, Diana Robiatul; Aeni, Naura Nur; Oktaviani, Tia Azzahra; Fahrezi, Fitroh; Suherman, Ujang (Jurnal Ilmiah Wahana Pendidikan, 2024)
The purpose of writing this article is to provide a deeper analysis of the factors influencing the interest of the younger generation in choosing Sharia mutual funds as an investment option. The method used is a descriptive method, adopting a secondary analysis approach through a review of literature from various related studies. The primary focus of this research is to explore and analyze the young generation's interest in Sharia mutual fund investments, with a specific emphasis on information and findings revealed in previous research literature. In the current investment context, there are many instrument options available, both conventional and Sharia. This includes not only real instruments such as precious metals, land, houses, and properties but also financial instruments such as securities in the money market and capital market. The potential of the Sharia mutual fund market is increasing, especially with the growth of the productive age population in Indonesia, dominated by Generation Z (born between 1997-2012). Data shows a significant increase in the number of individuals investing in mutual funds, from 1.77 million investors in 2019 to 2.7 million in October 2020, marking a 52.2% increase. Through literature review, particularly in the context of the young generation's interest in Sharia mutual fund investments in Surabaya, information is obtained indicating that factors such as motivation, financial literacy, and return on investment are the main drivers of their interest. Related articles highlight that the young generation's interest in Sharia mutual fund investments is not only based on financial motivation but also on a high level of understanding of the Sharia principles that form the basis of these investment instruments.